Stochastic Tension‐Stiffening Approach for the Solution of Serviceability Problems in Reinforced Concrete: Constitutive Modeling. (24th February 2015) - Gribniak, Viktor; Mang, Herbert Anton; Kupliauskas, Rimantas; Kaklauskas, Gintaris
Abstract A number of studies have indicated that the tension‐stiffening law is an important input parameter in a numerical analysis of serviceability (deformations and cracking) problems of reinforced concrete (RC) structures. The stochastic nature of concrete cracking, which results in a large scatter of experimental results, renders the constitutive modeling a very difficult task. Even data obtained from short‐term tests are to some degree uncertain due to time‐dependent processes occurring in concrete, such as shrinkage and creep relaxation. This article provides statistical analysis tools that can be readily applied to engineering practice. Stochastic principles are applied to modeling of tension‐stiffening for the purpose of predicting not only the average deformation response of RC elements, but also bounds of these predictions that are of vital importance for practical problems. Unlike common practice, shrinkage of concrete is taken into account in the short‐term numerical simulation.